FUKUSHIMA FALLOUT IN SAKHALIN REGION, RUSSIA, PART 3: 137CS AND 134CS IN COW’S MILK - V. P. Ramzaev; A. N. Barkovsky; A. V. Gromov; M. V. Kaduka (Радиационная гигиена)
The study was conducted on Kunashir, Shikotan and Iturup Islands (Sakhalin Region of Russia) in order to evaluate the impact of the Fukushima accident on the “soil–grass–cow’s milk” exposure pathway. A total of 22 samples of cow’s milk were collected in the May 2011 – September 2012 period. Radiocaesium was isolated from thermally treated specimens using the antimony–iodide radiochemical method. The activity concentrations of 134Cs and 137Cs were measured by γ-ray spectrometry using high purity germanium detectors. Caesium-134 was detected in 18 of the total 22 samples of milk. The activity concentration of 134Cs in the samples varied from 0.08 Bq kg–1 to 2.00 Bq kg–1. Caesium-137 was quantified in all 22 samples: range = 0.088–2.43 Bq kg–1. On average, more than a half of the total 137Cs in the milk samples from Sakhalin Region was of Fukushima origin (mean = 60%, median = 57%, range = 13–95%). The highest activity concentrations and values of the soil–to–milk aggregated transfer coefficient, Tag, for 134Cs (and Fukushimaderived 137Cs) were observed in milk samples collected in mid-May 2011. The mean Tag values decreased in the May–October period of 2011 from 12 × 10−3 m2 kg–1 to 2.3 × 10−3 m2 kg–1. In September 2012, the Tag values remained unchanged (mean = 2.8 × 10−3 m2 kg–1) compared to those in September–October 2011. In the autumns of 2011 and 2012, the calculated values of Tag for Fukushima-derived radiocaesium were on average 17 times larger than the ones for pre-Fukushima 137Cs. The higher transfer of Fukushima-derived 137Cs (compared to pre-Fukushima 137Cs) for milk reflected the difference between the “new” and “aged” radiocaesium in the intensity of the radionuclide transfer from soil to grassland plants which were the major component of the cow’s diet in the area of our study. The ratio between the 137Cs activity concentration in the milk (fresh weight) and that in the grassland plants (dry weight) ranged from 0.028 to 0.11. The effective dose from ingestion of Fukushima-derived radiocaesium in locally produced cow’s milk for critical group of adult residents of the southern Kuril in the first year after the accident is conservatively estimated as 0.0027 mSv. The Fukushima accident has had a negligible impact on radiocaesium contamination of cow’s milk and the corresponding human exposure on the southern Kuril Islands: Shikotan, Kunashir and Iturup.